Edukasi dan Pelatihan Yoga untuk Mengurangi Nyeri Haid Primer Bagi Remaja Putri - Indra Puspita; Andi Sriana; Intan Yemima; Tita Nadea Pratiwi Rahma; Ana Lestari Ningsih; Herlina Liling; Mirwana; Heni Hirawati Pranoto (Universitas Ngudi Waluyo, 2026)
Primary dysmenorrhea is a common health problem among adolescent girls and often disrupts daily activities. The usual management is the consumption of pain relievers, but non-pharmacological approaches such as yoga are still rarely known and practiced. This community service program aimed to increase adolescents’ knowledge about yoga as a complementary therapy to reduce primary menstrual pain so that adolescent girls are able to perform yoga movements independently to reduce pain and enhance comfort during menstruation. The program was conducted at SMPN 01 Peso and SMPN 03 Tana Tidung on May 22, 2026, involving 20 eighth-grade students. The methods included health education, yoga training, and evaluation of knowledge before and after the intervention. The results showed a significant improvement: prior to education, 80% of respondents had poor knowledge and 20% had moderate knowledge; after education, all respondents (100%) achieved good knowledge. These findings confirm that yoga education and training effectively enhance adolescents’ understanding of safe, independent, and non-pharmacological management of primary dysmenorrhea. This program is expected to be sustainably implemented in schools and adolescent health services to support reproductive health and improve the quality of life of adolescent girls. Abstrak Nyeri haid primer (dismenore) merupakan masalah kesehatan yang umum dialami remaja putri dan sering mengganggu aktivitas sehari-hari. Penanganan yang lazim dilakukan adalah konsumsi obat pereda nyeri, namun pendekatan non-farmakologis seperti yoga masih jarang diketahui dan diterapkan. Kegiatan pengabdian masyarakat ini bertujuan untuk meningkatkan pengetahuan remaja putri mengenai yoga sebagai terapi komplementer dalam mengurangi nyeri haid primer sehingga remaja putri mampu melakukan gerakan yoga secara mandiri untuk mengurangi nyeri dan meningkatkan kenyamanan selama menstruasi. Program dilaksanakan di SMPN 01 Peso dan SMPN 03 Tana Tidung pada 22 Mei 2026 dengan melibatkan 20 siswi kelas VIII. Metode kegiatan meliputi penyuluhan, pelatihan yoga, serta evaluasi pengetahuan sebelum dan sesudah intervensi. Hasil menunjukkan adanya peningkatan signifikan: sebelum edukasi, 80% responden memiliki pengetahuan kurang dan 20% cukup; setelah edukasi, seluruh responden (100%) mencapai kategori pengetahuan baik. Temuan ini menegaskan bahwa edukasi dan pelatihan yoga efektif meningkatkan pemahaman remaja putri tentang penanganan nyeri haid primer secara mandiri, aman, dan non-farmakologis. Program ini diharapkan dapat diterapkan secara berkelanjutan di sekolah maupun posyandu remaja untuk mendukung kesehatan reproduksi dan kualitas hidup remaja putri.